1995
DOI: 10.1128/aem.61.10.3752-3755.1995
|View full text |Cite
|
Sign up to set email alerts
|

Acid adaptation of Escherichia coli O157:H7 increases survival in acidic foods

Abstract: Escherichia coli O157:H7 was adapted to acid by culturing for one to two doublings at pH 5.0. Acid-adapted cells had an increased resistance to lactic acid, survived better than nonadapted cells during a sausage fermentation, and showed enhanced survival in shredded dry salami (pH 5.0) and apple cider (pH 3.4). Acid adaptation is important for the survival of E. coli O157:H7 in acidic foods and should be considered a prerequisite for inocula used in food challenge studies. Since 1982, food-related diarrheal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(165 citation statements)
references
References 20 publications
10
150
0
3
Order By: Relevance
“…Guraya et al (1998) reported that 10 5 CFU mL )1 of E. coli O157:H7 were eliminated at pH 3.8 in milk during 7 days and became undetectable (<10 CFU mL )1 ) at pH 4.1 after 35 days at 4°C. Kotz et al (1990) stated that Ôtheir studies demonstrate the bactericidal effect of yogurt is not solely to the acid pH, as milk acidified to the pH of yogurt (pH 4.4) is bacteriostatic for E. coli but not bactericidal.Õ In addition, acid adaptation of E. coli O157:H7 has been reported previously (Leyer et al, 1995). In the present study pH values at which E. coli O157:H7 were eliminated are in agreement with previous studies, but elimination times of the pathogen were shorter than those in previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Guraya et al (1998) reported that 10 5 CFU mL )1 of E. coli O157:H7 were eliminated at pH 3.8 in milk during 7 days and became undetectable (<10 CFU mL )1 ) at pH 4.1 after 35 days at 4°C. Kotz et al (1990) stated that Ôtheir studies demonstrate the bactericidal effect of yogurt is not solely to the acid pH, as milk acidified to the pH of yogurt (pH 4.4) is bacteriostatic for E. coli but not bactericidal.Õ In addition, acid adaptation of E. coli O157:H7 has been reported previously (Leyer et al, 1995). In the present study pH values at which E. coli O157:H7 were eliminated are in agreement with previous studies, but elimination times of the pathogen were shorter than those in previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…in acidified foods, such as apple cider and orange juice (that have pH values similar to many acidified pickled products) suggest that pickled vegetables may not be free from these pathogens (CDC 1996(CDC , 1999. Escherichia coli O157:H7 could be a pathogen of concern in acidified pickled vegetables because of its low infectious dose (Gorden and Samll 1993;Keene et al 1994), high acid tolerance (Glass et al 1992;Miller and Kaspar 1994;Benjamin and Datta 1995;Leyer et al 1995;Tsai and Ingham 1997) and severe consequences of infection such as hemorrhagic colitis and hemolytic uremic syndrome (Griffin and Tauxe 1991;Padhye and Doyle 1992). The growth or survival of E. coli O157:H7 in acid and acidified foods (pH £ 4AE5) has been reported in a variety of products, including mayonnaise (Weagant et al 1994;Raghubeer et al 1995), apple cider Zhao et al 1993) and fermented dairy products (Arocha et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables naturally contain one or more OAs and many vegetables that are commonly pickled are mildly acidic (pH ranging from 5AE1 to 6AE7). Foodborne pathogens that can grow on vegetables may adapt to the mild acidic conditions and develop inducible acid tolerance during growth in an acidic environment (Goodson and Rowbury 1989;Benjamin and Datta 1995;Leyer et al 1995;Gahan et al 1996;Tsai and Ingham 1997;Castanie-Cornet et al 1999;Michino et al 1999;Smittle 2000;Tetteh and Beuchat 2001).…”
mentioning
confidence: 99%